Aprendizagem significativa de função do 1º grau : uma investigação por meio da modelagem matemática e dos mapas conceituais - Luz, Silas Venâncio da (2010)
Leading students to learn mathematics meaningfully is the wish of any teacher. However, this task has some drawbacks: How to unleash the development of meaning by the students and how to collect evidence of this occurrence? This and other relevant issues, due to the fact they disturb our consciousness, prompted us to delineate the two questions in this research: Mathematical modeling environment is conducive to meaningful learning of 1° Degree Function in a class of first year of high school? How may the conceptual maps be used in a parallel way with the Mathematical Modeling for checking the evidence of the occurrence of Meaningful Learning of 1° Degree Function? From these two questions and theoretical frameworks adopted: the Theory of Meaningful Learning, the Conceptual Maps and the Mathematical Modeling; this research was done aiming to provide evidence by means of conceptual maps, of the occurrence of meaningful learning of the content of 1° Degree Function in a class of the first year of high school, through investigative activities guided by the environment of Mathematical Modeling. To this end, one of the classes of the first year of high school of the teacher-researcher was selected. It was chosen the one that best fitted to the process of developing conceptual maps, with which it was developed two mathematical modeling activities involving the concepts related to the 1° Degree function. In this investigation the students developed four conceptual maps: the first one about 1° Degree Function, the second and third ones about each of the two activities carried out and finally another map about the same opening theme. The analyses of all materials produced by the teams during the activities and of the individual maps developed by the students made it possible to state that the process of assimilation of the concept of 1° Degree function was unleashed in some students and, consequently, their learning became more significant after the development of the activities. Thus, we confirm the influence and cooperation of Mathematical Modeling and Conceptual Maps for the entire research process.